Odpowiedź :
a\ 3 -15x - 3x + 7 ≥ -2
-18x ≥ -12 /÷ -18
x ≤ ⅔
b\
c\ 3x - 4x² ≥ 8x - 4x²
0 ≥ x
d\
e\ -0,3x - 0,6 - 0,6x + 0,9 ≥ 0,1x /×10
-3x - 6 - 6x + 9 ≥ x
-8x ≥ -3 /÷ -8
x ≤ 3/8
f\ 2x - ¼ - 4 - 6x ≤ 1
-4x ≤ 5¼ /÷ -4
x ≥ 2 5/8
-18x ≥ -12 /÷ -18
x ≤ ⅔
b\
c\ 3x - 4x² ≥ 8x - 4x²
0 ≥ x
d\
e\ -0,3x - 0,6 - 0,6x + 0,9 ≥ 0,1x /×10
-3x - 6 - 6x + 9 ≥ x
-8x ≥ -3 /÷ -8
x ≤ 3/8
f\ 2x - ¼ - 4 - 6x ≤ 1
-4x ≤ 5¼ /÷ -4
x ≥ 2 5/8
a) 3-15x-3x+7 >/=-2
10-18x>/=-2 ?-10
-18x>/=-12 /-18
x</=12/18 = 2/3
e) -0,3x-0,6-0,6x+0,9>0,1x
-0,9x+0,3>0,1x
0,3>1x
0,3>x
c)3x-4x^2>8x-4x^2
3x>8x /-3x
o>5x /:5
0>x
f)2x-1/4-3-4i1/2x</=1
-2i 1/2x-13/4</=1
-13/4</=2i1/2x
-13/4<5/2x /*4
-13</=10x /:10
-1,3</=x
10-18x>/=-2 ?-10
-18x>/=-12 /-18
x</=12/18 = 2/3
e) -0,3x-0,6-0,6x+0,9>0,1x
-0,9x+0,3>0,1x
0,3>1x
0,3>x
c)3x-4x^2>8x-4x^2
3x>8x /-3x
o>5x /:5
0>x
f)2x-1/4-3-4i1/2x</=1
-2i 1/2x-13/4</=1
-13/4</=2i1/2x
-13/4<5/2x /*4
-13</=10x /:10
-1,3</=x